Revisiting the Origins of Ilm al-Kalam: Interreligious Dialogues and Their Impact on Islamic Educational Thought - Jelita, Dian; Islami, Nisa; Taufiqurrahman, Muhammad; Afriani, Zelvia Liska (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This article revisits the historical and interreligious origins of Ilm al-Kalam and explores its implications for contemporary Islamic educational thought. Drawing on Alexander Treiger’s seminal analysis in The Oxford Handbook of Islamic Theology, the study employs qualitative textual methods to examine the formative dialogues between early Muslim theologians and Arab Christian thinkers, revealing that Kalam developed through dynamic epistemological engagement rather than in isolation. By critically tracing its philosophical, theological, and pedagogical transformations across time, the study argues that Kalam’s rational and dialectical methodologies offer significant potential for revitalizing Islamic education. The findings highlight the limitations of internalist historiographies and call for a reimagined curriculum model that integrates historical consciousness, critical reasoning, and ethical responsibility. Positioned within a transdisciplinary framework, the article proposes that Ilm al-Kalam be recontextualized not merely as a theological discipline but as a living epistemic tradition capable of informing pedagogical innovation in the face of global educational and ethical challenges.